2018
DOI: 10.1149/2.0661802jes
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial Carbon Enhanced Corrosion Resistance of Fe-33Mn-xC Austenitic Steels: Inhibition of Anodic Dissolution

Abstract: Five Fe-33Mn-xC steels, referred to as 0 C, 0.3 C, 0.6 C, 0.8 C, and 1.1 C steels according to their carbon content in mass%, were prepared to clarify the effect of interstitial carbon on the dissolution behavior of steel. The 0.3 C, 0.6 C, 0.8 C, and 1.1 C steels indicated a fully austenitic structure with no carbide precipitate. The lattice parameters of the 0.6 C, 0.8 C, and 1.1 C steels calculated from the γ(111) and γ(200) diffraction peaks increased by up to around 0.8% over that of the 0.3 C steel, sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 45 publications
0
10
1
1
Order By: Relevance
“…More specifically, hydrogen-charging caused a 0.4% linear expansion of the (001) γ interplanar spacing, and 1.9% and 0.4% linear expansions of the ( 10 11 ) ε interplanar spacings, corresponding to the low and high angle parts of the split peak, respectively. Since even a linear expansion of the (001) γ interplanar spacing by 1.1 mass% carbon is 0.8%, 12) the 1.9% expansion of the (10 11 ) ε interplanar spacing is an abnormal phenomenon.…”
Section: Methodsmentioning
confidence: 99%
“…More specifically, hydrogen-charging caused a 0.4% linear expansion of the (001) γ interplanar spacing, and 1.9% and 0.4% linear expansions of the ( 10 11 ) ε interplanar spacings, corresponding to the low and high angle parts of the split peak, respectively. Since even a linear expansion of the (001) γ interplanar spacing by 1.1 mass% carbon is 0.8%, 12) the 1.9% expansion of the (10 11 ) ε interplanar spacing is an abnormal phenomenon.…”
Section: Methodsmentioning
confidence: 99%
“…This is might be due to the increase in surface roughness of the treated samples as a function of processing temperature [44]. It has been previously reported that the nitrogen and carbon has a beneficial effecting in improving the corrosion potential [45] [46]. Further, the solid solution γ C and γ N phases have more passivity than the austenite phase [26] [47].…”
Section: Corrosion Performancementioning
confidence: 99%
“…As a result, both the electrical and thermal conductivities are decreased in the carburized alloy. 42 Additionally, XPS results on the carburized alloys, including both martensitic and austenitic steels, 8,43 show that the electron binding energy of Fe atoms for the sample with high interstitial carbon is higher than that of the sample without interstitial carbon, which can also be attributed to the formation of covalent M-C bonds.…”
Section: Effect Of Interstitial Carbon On Bond Strength Of An Alloy Systemmentioning
confidence: 99%